P-195 PGE-MUM: Clinical Benefit of Monitoring of Ulcerative Colitis Patients Treatment Efficacy. (February 2017) - Arihiro, Seiji; Arai, Yoshinori; Hokari, Atsushi; Saruta, Masayuki; Matsuura, Tomokazu; Ito, Satoru; Fujiwara, Mutsunori; Okayasu, Isao
Abstract : Background: With the development of new therapeutic approaches, the ultimate goal of ulcerative colitis (UC) treatment is not only clinical remission but also mucosal healing. We have shown that PGE-MUM value is very useful biomarker for inflammation status of UC patients. We now ask whether PGE-MUM value reflects clinical status under different regimens of treatment or not. Methods: Thirteen patients (M/F = 6/7; age: average = 58.5 ± 10.5, 48.8 ± 11.4 yr) were monitored for more than 1 year at Jikei University. PGE-MUM measurement was performed by the PGE-MUM radioimmunoassay kit (Fujirebio, Inc.) as reported. Clinical activities were evaluated by simple clinical colitis activity index (SCCAI). Inflammatory status was also monitored with serum CRP values. Interventions were mostly 5-ASA treatment, but prednisolone, FK506, Cyclosporin A, anti-TNF-alpha agent were also applied. Results: Changes of PGE-MUM values correlated well with SCCAI during whole monitoring period. But CRP values did not correlate well, rather suppressed value with even higher score of SCCAI upon steroid prescription. Thus, CRP data did not necessarily reflect inflammatory status during steroid treatment. Also in case of pancreatitis patient (remission status of UC) CRP exhibited high value, but PGE-MUM did not show elevated value. Conclusions: PGE-MUM exhibited good correlation between SCCAI during monitoring whole period under different treatment regimen. But serum CRP sometimes exhibited different behavior from SCCAI upon steroid regimen, but not always. Thus, PGE-MUM is promising surrogate marker reflecting UC status upon different treatment regimens.